2011
DOI: 10.1021/ac202779h
|View full text |Cite
|
Sign up to set email alerts
|

MALDI Mass Spectrometric Imaging of Cardiac Tissue Following Myocardial Infarction in a Rat Coronary Artery Ligation Model

Abstract: Although acute myocardial infarction (MI) is consistently among the top causes of death in the United States, the spatial distribution of lipids and metabolites following MI remains to be elucidated. This work presents the investigation of an in vivo rat model of MI using mass spectrometric imaging (MSI) and multivariate data analysis. MSI was conducted on cardiac tissue following a 24-hour left anterior descending coronary artery ligation in order to analyze multiple compound classes. First, the spatial distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 47 publications
7
63
0
Order By: Relevance
“…MALDI-MSI has recently been applied in lipidome studies of human skin ( 8 ), veins ( 9 ), and ovary ( 10 ); mouse embryo implantation sites ( 11 ), tongue ( 12 ), and leg muscle ( 13,14 ); and rat spinal cord ( 15 ), cardiac tissue ( 16 ), and liver ( 17 ). Mammalian brain tissue, due to its high lipid content, has also been extensively studied by MSI.…”
Section: Tumor Dissection and Optical Imagingmentioning
confidence: 99%
“…MALDI-MSI has recently been applied in lipidome studies of human skin ( 8 ), veins ( 9 ), and ovary ( 10 ); mouse embryo implantation sites ( 11 ), tongue ( 12 ), and leg muscle ( 13,14 ); and rat spinal cord ( 15 ), cardiac tissue ( 16 ), and liver ( 17 ). Mammalian brain tissue, due to its high lipid content, has also been extensively studied by MSI.…”
Section: Tumor Dissection and Optical Imagingmentioning
confidence: 99%
“…Another application for MALDI-IMS is for discovering biomarkers.Menger et al [38 ]used it to reveal potential markers for myocardial infarction within intact cardiac tissue. The researchers reported that creatine, a metabolite involved in the creatine kinase metabolic pathway, demonstrated a decreased ion signal within the areas of infarcted tissue.…”
Section: Application Of Ims For Vascular Pathologymentioning
confidence: 99%
“…MALDI-MSI (31) has been applied in the study of animal and human tissues as a research tool as well as in a medical diagnostic capacity in the study of disease pathology (32)(33)(34) and to monitor drug pharmacokinetics (35,36). Recent examples of plant MALDI-MSI providing insights through spatial information include the peptide analytes of developing soybean cotyledons (37), secreted peptide hormones involved in plant development in Arabidopsis roots (38), and small-molecule glucosinolate derivatives involved in plant defense from Arabidopsis leaves (39).…”
mentioning
confidence: 99%